2021
DOI: 10.1371/journal.pone.0255155
|View full text |Cite
|
Sign up to set email alerts
|

Subnormothermic ex vivo lung perfusion attenuates ischemia reperfusion injury from donation after circulatory death donors

Abstract: Use of normothermic ex vivo lung perfusion (EVLP) was adopted in clinical practice to assess the quality of marginal donor lungs. Subnormothermic perfusion temperatures are in use among other solid organs to improve biochemical, clinical and immunological parameters. In a rat EVLP model of donation after circulatory death (DCD) lung donors, we tested the effect of four subnormothermic EVLP temperatures that could further improve organ preservation. Warm ischemic time was of 2 hours. EVLP time was of 4 hours. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
13
0
3
Order By: Relevance
“…Recent studies have shown numerous advantages to using subnormothermic temperature. 42,43 It is a compromise between full metabolism reached at normothermic temperature to low organ metabolism when hypothermic. Normothermic perfusion brings challenges in perfusate composition as it needs to deliver enough nutrients for full metabolism thus requiring added oxygen sources (oxygen carrier and/or blood cells).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recent studies have shown numerous advantages to using subnormothermic temperature. 42,43 It is a compromise between full metabolism reached at normothermic temperature to low organ metabolism when hypothermic. Normothermic perfusion brings challenges in perfusate composition as it needs to deliver enough nutrients for full metabolism thus requiring added oxygen sources (oxygen carrier and/or blood cells).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This suggests that the significant damage after W2h was mainly because of severe, potentially irreversible, ischemic injury but not because of amplification of nitro-oxidative stress and inflammatory signaling during EVLP. Because such, a W2h model may seem extremely stringent to evaluate pharmacological reconditioning for the repair of established ischemic injuries; however, this model has been used by some authors, who reported reconditioning effects of K-ATP channels modulators, 31 plasmin, 32 and subnormothermic EVLP 33 in rat lungs damaged by W2h.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gloria et al [ 43 ] and our group [ 44 , 45 ] presented evidences that rat lung grafts treated either with normothermic EVLP or without EVLP have a worst outcome than lung grafts treated before transplantation with subnormothermic EVLP temperatures. In this article, at 28 °C with or without PFCOC, we recorded a significantly lower amount of a selection of pro-inflammatory mediators (i.e., TNFα, IL-6, IL-7) and of chemokines (MIP-3α, MIP-1α, MCP-1, GRO/KC) in the perfusates.…”
Section: Discussionmentioning
confidence: 99%